Draft Tenth Five Year Plan (2002-2007) and Annual Plan (2002-2003) Planning Department Government of Andhra Pradesh - Planning Commission (Planning Commission, 2002)
Rs.54098.26 crores is the outlay proposed for the Tenth Five Year Plan and at 2001-2002 prices the outlay is proposed as Rs.46611.83 crores. Rs.10082.75 crores is the outlay for the Annual Plan 2002- 2003 and at 2001-2002 prices the outlay is proposed as Rs.9601.70 crores. Rs.28601.98 crores is the state's own resources, Rs.6829.49 crores is expected as normal central assistance to be released by the Planning Commission, Rs.5126.40 crores is the additional central assistance expected under different earmarked schemes and Rs.13540.39 crores is the additional central assistance under externally aided projects including Rs.4600 crores under A.P.Structural Adjustment Loan.
Planning Department, Government of Andhra Pradesh